2007
DOI: 10.1016/j.ijrobp.2007.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Function of Patients with Brain Metastasis Who Received Either Whole Brain Radiotherapy Plus Stereotactic Radiosurgery or Radiosurgery Alone

Abstract: PURPOSEIt is not well known how the omission of whole-brain radiotherapy (WBRT) affects the neurocognitive function of patients with 1-4 brain metastases who are treated with stereotactic radiosurgery (SRS). MATERIALS AND METHODSIn a prospective randomized trial between WBRT+SRS and SRS-alone in patients with 1-4 brain metastases, neurocognitive function was assessed by the Mini-Mental Score Examination (MMSE). Among 132 enrolled patients, MMSE scores were available for 110 patients. RESULTSIn the baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
304
3
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 497 publications
(320 citation statements)
references
References 26 publications
4
304
3
4
Order By: Relevance
“…However, to longterm survivors, WBRT could be a cause of continuous deterioration of neurological function (Aoyama et al, 2007). In another trail about NSCLC, Kundu S et al also shows that stereotactic body radiotherapy has minimal toxicity but good efficacy (Kundu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, to longterm survivors, WBRT could be a cause of continuous deterioration of neurological function (Aoyama et al, 2007). In another trail about NSCLC, Kundu S et al also shows that stereotactic body radiotherapy has minimal toxicity but good efficacy (Kundu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1,4,27,29,40 Additionally, brain metastases are particularly well suited for radiosurgery given that these lesions tend to have clear margins. 13 When used as a primary treatment for solitary metastasis, radiosurgery has been associated with local tumor control rates of 73%-94% and less morbidity than WBRT.…”
mentioning
confidence: 99%
“…Aoyama et al 13 (2007) used the mini-mental state examination to assess cognitive function, and found that the main factor related to cognitive function is tumor control. Cognitive worsening was earlier the single treatment group (7.6 months vs. 16.5 months, p=0.05).…”
Section: Resultsmentioning
confidence: 99%